Direct correlation between ischemic burden induced by dipyridamole and stress peak filling rate: a gated perfusion single-photon emission computed tomography study. Issue 2 (February 2021) - Bestetti, Alberto; Cuko, Besart; Gasparini, Massimo; De Servi, Stefano
Abstract : Aim and patients: The aim of the present study was to assess the effects of dipyridamole on stress and rest peak filling rate in consecutive patients who showed perfusion and, or function abnormalities at Gated-SPECT. Were enrolled 96 patients (73 males (76%); mean age 71.7 ± 9.57). Forty patients (41.7%) had an history of myocardial infarction and fifty-seven (59.4%) of previous cardiac revascularization. All patients underwent a 2-day 99mTc-SestaMIBI gated perfusion SPECT protocol. Results: Twenty-nine (30.2%) patients showed fixed perfusion defects, 54 (56.2%) showed partially or completely reversible ones, while 13 (13.5%) showed normal perfusion but reduced LVEF. SSS was significantly higher than SRS (9.55 ± 9.29 vs. 7.10 ± 8.48; P = 0.0001). Stress peak filling rate was not significantly higher than rest peak filling rate (1.73 EDV/s ± 0.69 EDV/s vs. 1.67 EDV/s ± 0.56 EDV/s; P = 0.62). At a multivariate regression analysis, only stress peak filling rate, as independent variable, was directly correlated with myocardial ischemia (SDS) ( P = 0.018). We divided patients according to SDS in those with mild (SDS < 5) and severe (SDS ≥ 5) ischemia. Stress peak filling rate was the only parameter significantly different between groups. Conclusion: Stress PFR showed a better correlation with the degree of ischemia compared to the remaining perfusion and functional parameters. The direct correlation between SDS and stress PFR leads us to speculate that dipyridamole could improve diastolic function in ischemic patients.